Social economic and demographic consequences of migration on Kerala - KC Zachariah ET Mathew Erudaya Rajan (International Migration (39) 2, 2001)
In Kerala, migration has contributed more to poverty alleviation and reduction in unemployment than any other factor. As a consequence, the State has become dependent on migration for employment, subsistence, housing, household amenities, institution building, and many other developmental activities. However, it is noted that Kerala workers seem to be losing out in international competition for jobs in the Gulf market. Corrective policies are needed urgently to raise their competitive edge over workers in competing countries in South and Southeast Asia. Since the center of the problem is Kerala workers' inability to compete with expatriates from other countries, the solution lies in equipping workers with better general education and job training. A two-fold approach is suggested: 1) improving the job skills of prospective emigrant workers through ad hoc training programs focused on the job market in Gulf countries, and 2) restructuring the educational system, taking into consideration the future demand of workers not only in Kerala but also in potential destination countries worldwide.